Komunikasi Teks ke Visual: Kerangka Teoretis Gamifikasi Untuk Pembelajaran - Komarudin; Fatkha, Magfirotul; Sujono, Ujon (Ad-DA'WAH, 2025)
This study examines aspects of visual design and game element concepts within the framework of enhancing the learning experience and student motivation. The focus is on traditional Al-Qur'an education, where learning is often textual and monologic, thus tending to decrease student learning motivation. This article develops a theoretical framework for the gamification of Al-Qur'an learning that integrates interactive visual elements to improve student engagement. The research method is a literature review based on Design-Based Research (DBR), a research paradigm that systematically designs, develops, and evaluates practical solutions. The results of the study produce a gamification design that considers Islamic values and the characteristic needs of the digital generation. The proposed framework includes a needs-based adaptive process, the utilization of digital platforms, and the strengthening of Islamic narrative elements. With appropriate design, gamification can transform Al-Qur'an learning from static text into an enjoyable visual experience, thereby expected to increase learning motivation in Islamic educational environments.